CONTEMPORARY APPROACHES TO MODERNIZATION IN ASIAN AND EASTERN COUNTRIES IN THE ERA OF GLOBALIZATION - Bakhtiyor Omonov (Western European Studies, 2025)
This article explores the evolution of "economic miracles" and the process of political modernization in the countries of Southeast Asia (such as China, Japan, India, Turkey, and others). It delves into the various models of development implemented in these regions, identifying key features and distinctive aspects of their modernization processes. The article examines how the combination of traditional values and Western technological advancements has shaped the trajectory of these nations. The findings are based on scientific analysis and offer valuable insights for policymakers, economists, and scholars from CIS member states. The study also highlights the role of foreign experience as a significant resource for understanding the socio-economic transformations in the context of globalization.
Keywords: society; modernization; Southeast Asia